Evaluation of superconducting features and gap coefficients for electron–phonon couplings properties of MgB2 with multi-walled carbon nanotube addition - Kaya, N.; Cavdar, S.; Ozturk, O.; Yildirim, G.; Koralay, H. (Springer Science and Business Media LLC, 2022)
In this study, the samples are prepared by solid state reaction method at different weight ratios (0-4%). The characterization of materials produced is conducted with the aid of powder X-ray diffraction (XRD), temperature-dependent electrical resistivities (rho-T) and magnetization (M-H) measurements. Moreover, the change in the scattering/breaking of cooper-pairs in the small homogeneous clusters in the superconducting paths with the addition of multi-walled carbon nanotube is also examined by the energy gap coefficients. All the experimental findings show that the weight ratio of wt 2% is observed to be the optimum addition level. The XRD results indicate that the MgB2 material prepared by the optimum level crystallizes better in hexagonal symmetry. The critical current density is found to increase from 1.0 x 10(4) to 2.3 x 10(4)A cm(-2) depending on the increment in the magnetization values. On the other hand, the addition mechanism is noted to degrade slightly the general electrical features, critical transition temperatures, lattice cell constants and crystallite size of MgB2 material. Regardless, although the carbon nanotube addition seems to be negative effect on some general properties, the fundamental characteristic properties (the crystallinity with smoother crystallographic transition, magnetization values, coupling of adjacent layers, degree of broadening and especially formation of effective nucleation centers for the flux pinning ability) improve seriously at the optimum dopant level. Thus, the MgB2 prepared with the optimum carbon nanotube concentration can exhibit higher performance against the magnetic field and current in larger magnetic field strengths applied.
Keywords: Thin-Films; Enhancement; Critical-Current Density; Transport; Substitution; Microstructure; Bulk Mgb2